1994
DOI: 10.1063/1.466695
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of C+16 to C+36 photodissociation

Abstract: Photofragmentation of mass-selected C+16 to C+36 clusters is investigated at two laser wavelengths: 532 and 355 nm. The depletion dependence on laser fluence leads to the number of absorbed photons, together with the photoabsorption cross section. From the knowledge of the internal energy deposited in the clusters before the fragmentation step, the dissociation energies are deduced. Clusters C+16 to C+29 are found to be less and less stable, whereas above C+30 an increased stability is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
16
1
Order By: Relevance
“…This is perhaps not too surprising because previous work has long suggested that this is the most abundant molecule in the vapor above carbon in a vacuum, 1,5 and it is well known that C 3 is a stable neutral fragment in the 11 decomposition of small carbon clusters. [23][24][25][26][27][28][29][30] However, ours is the first experiment with photon energies great enough to detect the small carbon clusters produced in such a laser vaporization experiment. It is also interesting that we detect only a very small intensity for C 2 + .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is perhaps not too surprising because previous work has long suggested that this is the most abundant molecule in the vapor above carbon in a vacuum, 1,5 and it is well known that C 3 is a stable neutral fragment in the 11 decomposition of small carbon clusters. [23][24][25][26][27][28][29][30] However, ours is the first experiment with photon energies great enough to detect the small carbon clusters produced in such a laser vaporization experiment. It is also interesting that we detect only a very small intensity for C 2 + .…”
Section: Resultsmentioning
confidence: 99%
“…For example, both C 5 + and C 6 + species produce C 3 + via fragmentation. [23][24][25][26][27][28][29][30] However, the thresholds for these fragmentation processes lie at 4-5 eV, 30 and so these processes could not contribute to the C 3 + channel until the photon energy is at least this far above the ionization thresholds of these clusters. As we show below, the ionization thresholds for C 5 and C 6 lie in the 9.5-10.0 eV range, and therefore one photon ionization accompanied by fragmentation would not be expected until photon energies above about 14 eV.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The decay of excited small carbon clusters has been experimentally widely studied [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In these experiments, the loss of neutral C 3 has been found to be the dominant dissociation process for both charged and neutral clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental set-up is essentially the same as that described in ref. 23. It is shown schematically in Fig.…”
Section: Methodsmentioning
confidence: 99%